Benzylamides and piperazinoarylamides of ibuprofen as fatty acid amide hydrolase inhibitors. (1st January 2019) - Deplano, Alessandro; Cipriano, Mariateresa; Moraca, Federica; Novellino, Ettore; Catalanotti, Bruno; Fowler, Christopher J.; Onnis, Valentina
Abstract: Fatty Acid Amide Hydrolase (FAAH) is a serine hydrolase that plays a key role in controlling endogenous levels of endocannabinoids. FAAH inhibition is considered a powerful approach to enhance the endocannabinoid signalling, and therefore it has been largely studied as a potential target for the treatment of neurological disorders such as anxiety or depression, or of inflammatory processes. We present two novel series of amide derivatives of ibuprofen designed as analogues of our reference FAAH inhibitor Ibu-AM5 to further explore its structure-activity relationships. In the new amides, the 2-methylpyridine moiety of Ibu-AM5 was substituted by benzylamino and piperazinoaryl moieties. The obtained benzylamides and piperazinoarylamides showed FAAH inhibition ranging from the low to high micromolar potency. The binding of the new amides in the active site of FAAH, estimated using the induced fit protocol, indicated arylpiperazinoamides binding the ACB channel and the cytosolic port, and benzylamides binding the ACB channel.